Recommendation System of Self-Medication for Mild Digestive Diseases with Dempster Shafer Method - Sayekti Abriani; Khurin 'ien Mukhoyyaroh; Ahmad Subhan Yazid; Maria Ulfah Siregar (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2014)
Pain is a state of body discomfort. To cure diseases, people usually go to the doctor, but now if the disease is mild it can be treated with self-medication. Therefore, Self-medication (Swamedikasi) recommendation system needs to be built specially to lessen and solve the mild disease problem, in this case, is digestion. The recommendation generated using an expert system with Dempster Shafer method. The application’s output will display the possibility of mild disease in digestion system that suffered by user based on the existing symptoms. The application also shows the possibility of symptoms from the legible disease that suffered by the user. The trust value obtained by using the Dempster Shafer method.